Participation as Capacity-Building for Active Citizenship - Chawla, Louise (Les ateliers de l'éthique / The Ethics Forum, 2009)
Within the framework of the “capability approach” to human rights, this paper argues that adults who facilitate participatory planning and design with children and youth have an ethical obligation to foster young people’s capacities for active democratic citizenship. Practitioners often worry, justifiably, that if young people fail to see their ideas realized, they may become disillusioned and alienated from political life. Based on the experience of the Growing Up in Cities program of UNESCO, four rules of good practice are distilled which can help promote young people’s belief in the value of collective action, regardless of the challenges that the full implementation of their ideas may face.